Mitigating opioid errors in inpatient palliative care: A qualitative study. Issue 3 (June 2020) - Heneka, Nicole; Bhattarai, Priyanka; Shaw, Tim; Rowett, Debra; Lapkin, Samuel; Phillips, Jane L.
Abstract: Background: Opioids are a high-risk medicine used in high doses and volumes in specialist palliative care inpatient services to manage palliative patients' pain and other symptoms. Despite the high volume of opioid use in this care setting, serious errors with opioids are exceedingly rare. However, little is known about the factors that mitigate opioid errors in specialist palliative care inpatient services. Aim: To explore palliative care clinicians' perceptions of factors that mitigate opioid errors in specialist palliative care inpatient services. Methods and design: A qualitative study using focus groups and semi-structured interviews. Participants and setting: Registered nurses, doctors, and/or pharmacists ('clinicians') who were involved with and/or had oversight of the services' opioid delivery and/or opioid quality and safety processes, employed by one of three specialist palliative care inpatient services in metropolitan NSW. Findings: Fifty-eight participants took part in this study, three-quarters (76%) of which were palliative care nurses. A positive opioid safety culture was central to mitigating opioid errors in specialist palliative care inpatient services. This culture of opioid safety was founded on clear and consistent safety messages from leadership, clinicians empowered to work together and practise safely, and a non-punitive approach to errors when they occurred. The clinical nurse educator was seen as pivotal to shaping, driving and reinforcing safe opioid delivery practices across the palliative care service. Conclusion: Creating and sustaining a positive opioid safety culture, and promoting a non-punitive approach to opioid error and reporting, is essential to mitigating opioid errors in the specialist palliative care inpatient setting.